2012
DOI: 10.3390/ijms13021846
|View full text |Cite
|
Sign up to set email alerts
|

The -308G/A of Tumor Necrosis Factor (TNF)-α and 825C/T of Guanidine Nucleotide Binding Protein 3 (GNB3) are Associated with the Onset of Acute Myocardial Infarction and Obesity in Taiwan

Abstract: Acute myocardial infarction is a highly prevalent cardiovascular disease in Taiwan. Among several etiological risk factors, obesity and inflammation are strongly associated with the frequency of hypertension, cardiovascular disease, diabetes, and myocardial infarction. To discriminate obesity- and inflammation-related genes and the onset of acute myocardial infarction (AMI), a case-control study was conducted to investigate the association of the -308G/A polymorphisms of tumor necrosis factor (TNF)-α and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…Chang et al also proved that TNF-a-308 G>A gene polymorphism was associated with obesity, 11 whereas Sobti et al reported that the AA and GA genotypes of TNF-a 308 G>A were associated with a higher risk of obesity in men; in women, only the AG genotype was associated with a higher risk of developing this nutritional disorder. The AA and GA homozygotes were also observed to present a higher risk for developing obesity-associated metabolic syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al also proved that TNF-a-308 G>A gene polymorphism was associated with obesity, 11 whereas Sobti et al reported that the AA and GA genotypes of TNF-a 308 G>A were associated with a higher risk of obesity in men; in women, only the AG genotype was associated with a higher risk of developing this nutritional disorder. The AA and GA homozygotes were also observed to present a higher risk for developing obesity-associated metabolic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Chang proved that TNF-a 308 G/A polymorphism is associated with obesity. 11 Based on the above-mentioned hypotheses, by using BMI as a relevant indicator of nutritional status, the present research aimed: i) to determine whether TNF-a 308G>A gene polymorphism is associated with overweight status, ii) to determine whether TNF-a 308G>A gene polymorphism is related to anthropometric (body mass index (BMI), mid-upper arm circumference (MUAC), and tricipital skinfold thickness (TST)) and biochemical (proteins, cholesterol, triglycerides, and lipids) variables, and iii) to quantify the influence of the studied gene polymorphism on overweight risk in children by assessing certain laboratory variables (cholesterol, LDL cholesterol, aspartate aminotransferase (ASAT), alanine aminotransferase (ALAT), and glycemia (Gly).…”
Section: Introductionmentioning
confidence: 99%
“…Controversially, Chang et al [29] and El Naggar et al [30] suggested that TNF-α-308 A>G is associated with increased risk of CAD and MI with other metabolic diseases like obesity and type 2 diabetes mellitus. They explained that the G to A substitute of -308 nucleotide located in the promoter region of the TNF-α gene alters its mRNA transcription level and contributes to raise TNF-α secretion in serum.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a multifunctional cytokine; as a key inflammatory mediator of AMI, TNF-α has been the subject of increased research. Animals overexpressing TNF suffer from severe heart disease, including arrhythmia (26)(27)(28). This indicates that upregulation of TNF expression is closely associated with the dysfunction of cardiac myocytes (29,30).…”
Section: Discussionmentioning
confidence: 99%